Sprawozdanie z międzynarodowej konferencji naukowej w Wiśle „Literatura obu Ameryk II” - Fiedeń, Anna (Tematy i Konteksty, 2015)
The report summarizes the International Academic Conference ‘Literature of Both Americas II’ (‘Literatura Obu Ameryk II’) which was held by the Faculty of Philology of the University of Silesia (Katowice) from 17 to 19 November 2014. It was the second conference of the series, which this time took place in picturesque Wisła and gathered researchers of migrant literature from both Poland and abroad. The multitude and variety of research areas presented not only supported their multidimensional exploration, but also once again showed that the issue of migrant literature in historical and literary research is reaching ever-widening circles. The conference in Wisła presented both a panoramic and detailed account of Polish literature in Canada and the United States, but still it paid attention to the need for focusing on the less explored issue of Polish literature in Latin and South America.